EMG analysis and vibration for assessment of propioceptors functions - Bosco, C.
To evaluate the proprioceptors capacity to function properly several subjects who have been previously (at lest one year before) operated in one leg, were exposed to vertical sinusoidal whole body vibration (WBV) for 60s. During the vibration treatment the EMGrms activity of leg extensor muscles leg extensor muscles (mm. vastus lateralis: LL (left) and LR (right) and vastus medialis: ML and MR) were simultaneously monitored in both normal and operated legs.